Structural analysis of natural killer cell receptor protein 1 (NKR-P1) extracellular domains suggests a conserved long loop region involved in ligand specificity - Sovová, Zofie; Kopecký, Vladimír; Pazderka, Tomáš; Hofbauerová, Kateřina; Rozbeský, Daniel; Vaněk, Ondřej; Bezouška, Karel; Ettrich, Rüdiger (Journal of molecular modeling, 2011)
Receptor proteins at the cell surface regulate the ability of natural killer cells to recognize and kill a variety of aberrant target cells. The structural features determining the function of natural killer receptor proteins 1 (NKR-P1s) are largely unknown. In the present work, refined homology models are generated for the C-type lectin-like extracellular domains of rat NKR-P1A and NKR-P1B, mouse NKR-P1A, NKR-P1C, NKR-P1F, and NKR-P1G, and human NKR-P1 receptors. Experimental data on secondary structure, tertiary interactions, and thermal transitions are acquired for four of the proteins using Raman and infrared spectroscopy. The experimental and modeling results are in agreement with respect to the overall structures of the NKR-P1 receptor domains, while suggesting functionally significant local differences among species and isoforms. Two sequence regions that are conserved in all analyzed NKR-P1 receptors do not correspond to conserved structural elements as might be expected, but are represented by loop regions, one of which is arranged differently in the constructed models. This region displays high flexibility but is anchored by conserved sequences, suggesting that its position relative to the rest of the domain might be variable. This loop may contribute to ligand-binding specificity via a coupled conformational transition.
Keywords: termodynamika; Molecular Sequence Data; Protein Structure, Tertiary; Rats; sekvence aminokyselin; Spectrum Analysis, Raman; spektroskopie infračervená s Fourierovou transformací; Sequence Alignment; myši inbrední C57BL; Mice, Inbred C57BL; Amino Acid Motifs; Mice; strukturní homologie proteinů; NK Cell Lectin-Like Receptor Subfamily B; Molecular Dynamics Simulation; aminokyselinové motivy; lektinové receptory NK-buněk - podrodina B; krysa rodu Rattus; konzervovaná sekvence; Thermodynamics; Spectroscopy, Fourier Transform Infrared; vazebná místa; zvířata; Humans; Binding Sites; Amino Acid Sequence; fylogeneze; Structural Homology, Protein; simulace molekulární dynamiky; myši; molekulární sekvence - údaje; Conserved Sequence; sekvenční seřazení; Phylogeny; terciární struktura proteinů; Ramanova spektroskopie; lidé; Animals